GOVERNMENT POLICIES AND SUSTAINABILITY OF SMALL AND MEDIUM ENTERPRISES (SMES) IN NORTH CENTRAL NIGERIA - David, Nweke Chukwubuikem; Ogedengbe, Frank Alaba; Gambo, Nasamu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The aim to systematically investigate the impact of government policies on the sustainability of SMEs in North Central Nigeria. The study adopted a cross-sectional research design to collect data at a single point in time, enabling an assessment of the impact of government policies on the sustainability of SMEs in North Central Nigeria. The study focuses on SMEs operating across states in Nigeria’s North-central geopolitical zone, specifically Benue, Kogi, Kwara, Nasarawa, Niger, Plateau, and the Federal Capital Territory (FCT). The population consists of SMEs classified by SMEDAN (Small and Medium Enterprise Development Agency of Nigeria) across the selected states is 218,434, with variations in distribution. Thus, using Yamane’s method, the sample sizes for each state range from 393 to 394. Stratified random sampling is adopted to ensure proportional representation across SME subgroups, minimizing bias and enhancing generalizability. This study rely exclusively on primary data collected through a structured survey to address the research objectives. This study employed multiple regression analysis to examine the impact of government policies on the sustainability of medium enterprises in North Central Nigeria. Based on the comprehensive data analysis, the following conclusions are drawn Taxation Policy Efficiency has a statistically significant positive impact on SME sustainability and Government Financial Incentives have a statistically significant positive impact on sustainability. In light of the conclusions, the study recommends that government should move beyond mere tax incentives and prioritize a holistic Tax Administration Reform and there is an urgent need to Streamline and Digitize Access to Financial Incentives.